2016
DOI: 10.1088/0029-5515/56/9/092012
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of runaway electrons, transport affected by J-TEXT resonant magnetic perturbation

Abstract: The topology of a magnetic field and transport properties of runaway electrons can be changed by a resonant magnetic perturbation field. The J-TEXT magnetic topology can be effectively altered via static resonant magnetic perturbation (SRMP) and dynamic resonant magnetic perturbation (DRMP). This paper studies the effect of resonant magnetic perturbation (RMP) on the confinement of runaway electrons via simulating their drift orbits in the magnetic perturbation field and calculating the orbit losses for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Note that the microseconds time scale of fast RE loss in this DIII-D experiment, identified as largely drift orbit loss due to large perturbation amplitude, is different from a previous modeling for DIII-D [17], where more than one order of magnitude smaller 3D perturbation field is in presence, and consequently the RE confinement time (∼100 µs or longer) is much longer than the prompt loss time shown in this study. Significant RE mitigation, observed in J-TEXT RMP experiments, has been explained by the drift loss [20], similar to this study.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Note that the microseconds time scale of fast RE loss in this DIII-D experiment, identified as largely drift orbit loss due to large perturbation amplitude, is different from a previous modeling for DIII-D [17], where more than one order of magnitude smaller 3D perturbation field is in presence, and consequently the RE confinement time (∼100 µs or longer) is much longer than the prompt loss time shown in this study. Significant RE mitigation, observed in J-TEXT RMP experiments, has been explained by the drift loss [20], similar to this study.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…The JOREK modeling [18] finds that REs, initialized before the TQ, can partially survive the magnetic field stochasticity generated during the TQ, and the survival rate depends on the electron energy range. 3D RMPs, without [19,21] or with [20] inclusion of the plasma response, were also found to modify the RE confinement in small-size tokamaks [19,20] as well as in ITER [21]. The effect of RMP on RE deconfinement is generally expected to be weaker in ITER than that in small size tokamaks such as COMPASS, where large perturbation field, of order δB/B ∼ 10 −2 , was found to induce clear RE loss in recent experiments [22] .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on Hamiltonian guiding center equations for runaway electrons, the effect of resonant magnetic perturbation (RMP) on the confinement of runaway electrons is simulated by calculating the orbit losses for different runaway initial energies and different runaway initial locations based on the J-TEXT plasma equilibrium [42]. The result indicates that the loss rate of runaway electrons is sensitive to the radial position of electrons as shown in figure 15.…”
Section: Observations Of Behavior Of Runaway Current Due To Rmpsmentioning
confidence: 99%
“…Past studies have demonstrated the feasibility of RE deconfinement via the application of 3D fields, both with regards to ideal tokamak theory [7,8], experimental demonstration [9][10][11], and predictions for ITER operation [12]. These nonaxisymmetric fields, whether generated in external coils or through intrinsic MHD dynamics of the plasma itself, cause some fraction of the runaway population to undergo drift orbit motion in the radial direction which eventually results in loss to the plasma limiter surface.…”
Section: Introductionmentioning
confidence: 99%